DETERMINAN PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) PADA PERUSAHAAN DI JAKARTA ISLAMIC INDEX (JII) - Yeney Widya Prihatiningtias; Elok Riskika Putri; Nurkholis Nurkholis; Wiwik Hidajah Ekowati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2022)
This study empirically analyzes the factors affecting Islamic Social Reporting (ISR), including profitability, liquidity, industry type, board of commissioner size, and company size. ISR, based on its category, is measured using ISR Index assessed from the companies’ annual report. The populations are all companies listed in Jakarta Islamic Index (JII) in 2017-2019. The samples include 17 companies selected through purposive sampling method, and are analyzed by multiple regression method. The results of this study indicate that the type of industry and company size have a significant effect on ISR; whilst, the profitability, liquidity, and board of commissioner size have no significant effect on ISR because manufacturing industry tends to be wider in disclosing its social responsibility reports, and this is also the case with large companies. This may be because the larger the size of the company, the larger the stakeholder community that must be served. Furthermore, profitability, liquidity, and the size of the board of commissioners have no significant effect on ISR because the company's orientation may be purely on profit or other financial aspects and the quality of ISR is not determined mainly by the quantity of the board of commissioners but may be caused by the quality or diversity of its members.